Elevated Serum Creatine Kinase and Small Cerebellum Prompt Diagnosis of Congenital Muscular Dystrophy due to FKRP Mutations. (March 2014) - Trovato, Rosanna; Astrea, Guja; Bartalena, Laura; Ghirri, Paolo; Baldacci, Jacopo; Giampietri, Matteo; Battini, Roberta; Santorelli, Filippo M.; Fiorillo, Chiara
Fukutin-related protein (FKRP) is a putative glycosyltransferase that mediate O -linked glycosylation of the α-dystroglycan. Mutations in the FKRP gene cause a spectrum of diseases ranging from a limb girdle muscular dystrophy 2I (LGMD2I), to severe Walker-Warburg or muscle-eye-brain forms and a congenital muscular dystrophy (with or without mental retardation) termed MDC1C. This article reports on a Moroccan infant who presented at birth with moderate floppiness, high serum creatine kinase (CK) levels, and brain ultrasonograph suggestive of widening of the posterior fossa. Muscle biopsy displayed moderate dystrophic pattern with complete absence of α-distroglycan and genetic studies identified a homozygous missense variant in FKRP . Mutations in FKRP should be looked for in forms of neonatal-onset hyperCKaemia with floppiness and small cerebellum.